Ceara PforR : Full Fiduciary Systems Assessment - World Bank (Washington, DC, 2014)
This assessment refers to the fiduciary arrangements governing the program-for-results (PforR) program. The fiduciary assessment found that the procurement and financial management arrangements are in line with OP 9.00 and that the capacity and performance of the implementing agencies are adequate for the purposes of the program. For procurement, the federal framework of laws and regulations is solid and transparent, and is familiar to both public officials and to the private sector. All procurement opportunities, regardless of estimated cost, are published via the internet. This involves establishing a local office or designating a local agent to serve as local representative and obtaining a taxpayer identification number or cadastro nacional de pessoas juridicas (CNPJ).